EFEKTIVITAS DIMENSI INTERNAL KEPALA SEKOLAH DALAM KEPEMIMPINAN PEMBELAJARAN - Sri Surachmi (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: The Effectiveness of the Principal’s Internal Dimensions in the Instructional Leadership. This study aims to investigate and analyze the effectiveness of internal dimensions related to the principal’s instructional leadership in SMP Negeri 2 Glagah, Banyuwangi. This study involved 140 participants as the sample, selected using the purpose sampling technique. The data were collected using a Likert-scale questionnaire and were analyzed using the descriptive technique. The results indicated that the internal dimensions were very effective, shown by (1) the indicator of the school’s mission, with a score of 516.3 and a percentage of 93.939%; (2) the indicator of the instructional organization with a score of 525.5 and a percentage of 93. 839%; (3) the indicator of instructional practice improvement with a score of 511.0 and a percentage of 91.25%; and (4) the indicator of positive school climate improvement with a score of 490.6 and a percentage of 87.611%. On the whole, the mean score of internal dimensions related to instructional leadership was 510.85 with a percentage of 91.22 %. Keywords: effectiveness, instructional leadership, internal dimensions